Effect of Rosemary Extract on the Chemical Composition and Quality Properties of Buffalo Burger During Cold Storage - Ahmed Abdulrahem, Batool Abdulrahem; Ahmed, Mahmoud Mohamed; Khalaf Al-Zaidi, Raed Mohammed (International Journal of Aquatic Research and Environmental Studies, 2026)
The current study aimed to use buffalo meat as an alternative to beef in the preparation of burgers. Compared to beef and sheep meat, this meat has first-class chemical, biological and nutrition characteristics, such as its fat, cholesterol, amino acids, vitamins and mineral components and positive effects on the health of humans. The findings suggest that buffalo meat is a healthy substitute to beef even in the case of a healthy person under some circumstances like pregnancy and so on as well as the people susceptible to cardiovascular and cerebrovascular diseases. The active compounds in rosemary extract were added to buffalo meat because it is known to preserve food better and keep the human organism fit. The chemical composition, sensory, and qualitative properties of the obtained burger were investigated with a refrigerated storage of (15) days. The content of buffalo meat in moisture, protein, fat and ash was (74.8, 21.3, 1.9, 1.03)%, respectively as shown in the study. It was also characterized by lower cholesterol content than that of beef since it was 45 per cent mg/ 100 g.